2006
DOI: 10.1177/107110070602701004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiographs and CT Scans in the Prospective Evaluation of the Fusion of Hindfoot Arthrodesis

Abstract: We believe the progress of the fusion cannot be determined accurately from standard radiographs. CT scanning appears to be significantly more reliable. The concept of what constitutes an adequate fusion deserves more extensive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 32 publications
(96 reference statements)
3
97
0
1
Order By: Relevance
“…Patient-reported outcome measures are being increasingly used to assess patient outcomes after medical and surgical procedures (22), and SF-12 has been widely studied to assess the clinical results after foot and ankle procedures (23)(24)(25). In the present study, the SF-12 physical and mental component scores at the last follow-up visit were 52.5 and 56.4, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…Patient-reported outcome measures are being increasingly used to assess patient outcomes after medical and surgical procedures (22), and SF-12 has been widely studied to assess the clinical results after foot and ankle procedures (23)(24)(25). In the present study, the SF-12 physical and mental component scores at the last follow-up visit were 52.5 and 56.4, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, it should be noted that in this study all patients with a hindfoot arthrodesis were deemed to have achieved bony union on the basis of clinical examination and radiographic analysis. Coughlin et al 5 demonstrated in a series of hindfoot arthrodeses that standard radiographs substantially overestimate the rate of hindfoot fusion when compared to computed tomography (CT) and showed CT scans are significantly more reliable in determining bony union. Given that radiographs were used as the sole imaging modality to assess union in our patients, it is possible that some patients in the fusion group had unappreciated nonunions that may have served as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…2 While the current study validates the utility of CT scan interpretation of joint fusion among orthopaedic surgeons, several limitations need to be acknowledged. This is a purely retrospective, radiographic study, with no clinical correlation to identify what can be considered a successful outcome.…”
Section: Discussionmentioning
confidence: 88%